The Effect Of Capital Aset And Liability Ratio On Non-Performing Loan - Herman Ruslim; Christopher Hartawan Bengawan (Jurnal Akuntansi, 2019)
The purpose of this study is to analyze the effect of capital adequacy ratio (CAR), loan to deposit ratio (LDR) and inefficiency on non-performing loans at commercial banks in Indonesia. The population used as the object of research amounted to 45 banks, while only 41 banks that fit the research criteria and serve as a research sample. The research period is 2016-2018, so the amount of data observed is 123 data. This study uses panel data with secondary data types. This research was processed by multiple linear analysis of panel data with the help of software e-views version 9.00. The result showed that CAR, LDR, and inefficiency simultaneously affected NPL. Partially, CAR showed a negative result but does not significantly influence NPL. While LDR and inefficiency proved to be a positive and significant effect on NPL.